2023
DOI: 10.1093/plcell/koad051
|View full text |Cite
|
Sign up to set email alerts
|

An ancestral role for 3-KETOACYL-COA SYNTHASE3 as a negative regulator of plant cuticular wax synthesis

Abstract: The plant cuticle, a structure primarily composed of wax and cutin, forms a continuous coating over most aerial plant surfaces. The cuticle plays important roles in plant tolerance to environmental stress, including stress imposed by drought. Some members of the 3-KETOACYL-COA SYNTHASE (KCS) family are known to act as metabolic enzymes involved in cuticular wax production. Here we report that Arabidopsis (Arabidopsis thaliana) KCS3, which was previously shown to lack canonical catalytic activity, instead funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 68 publications
0
13
2
Order By: Relevance
“…The KCSs in subclasses α, β, γ, δ and ϵ are known to possess catalytic activity, because they could display activity in various heterologous yeast expression systems ( Blacklock and Jaworski, 2006 ; Paul et al., 2006 ). However, the KCS3 in Arabidopsis thaliana belongs to subclass θ, and it plays a negative regulator of wax metabolism by reducing the enzymatic activity of KCS6, a key KCS involved in wax production ( Huang et al., 2023 ). KCSs in Oryza sativa were not classified into β and θ; it is possible that most of the KCS in rice have catalytic activity, which needs further experimental verification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KCSs in subclasses α, β, γ, δ and ϵ are known to possess catalytic activity, because they could display activity in various heterologous yeast expression systems ( Blacklock and Jaworski, 2006 ; Paul et al., 2006 ). However, the KCS3 in Arabidopsis thaliana belongs to subclass θ, and it plays a negative regulator of wax metabolism by reducing the enzymatic activity of KCS6, a key KCS involved in wax production ( Huang et al., 2023 ). KCSs in Oryza sativa were not classified into β and θ; it is possible that most of the KCS in rice have catalytic activity, which needs further experimental verification.…”
Section: Discussionmentioning
confidence: 99%
“…KCS4 is involved in the differential accumulation of polyunsaturated TAGs under stress ( Luzarowska et al., 2023 ). The mutants do not contain C20 and C22 VLCFAs and lead to C18 accumulation ( James et al., 1995 ); KCS2 and KCS20 are highly expressed in root endothelium, mainly producing C22 and C24 VLCFAs ( Lee et al., 2009 ); KCS5 and KCS6 ( CER6 ) play important roles in C24–C28 VLCFAs ( Millar et al., 1999 ), and KCS3 – KCS6 module affects wax synthesis ( Huang et al., 2023 ); KCS9 was the highest expressed in Arabidopsis stem epidermal cells, and the C24 VLCFA of the mutant was significantly reduced ( Kim et al., 2013 ). At present, there are few studies on the function of KCS genes in rice.…”
Section: Introductionmentioning
confidence: 99%
“…This provides further evidence that CYP96A4 and MAH1 (CYP96A15) have different functions in the alkane-forming pathway, potentially related to MAH1 and CYP96A4 competitively binding to alkanes. Our recent studies revealed that KCS3, homolog of KCS6, can interact with KCS6 to negatively regulate its activity in the synthesis of VLCFA and wax (Huang et al, 2023). Therefore, a similar mechanism might be also possible for CYP96A4 and MAH1, which is appreciated for further investigation.…”
Section: Discussionmentioning
confidence: 92%
“…The negative and positive controls were CYP96A4-Cub with NubG and NubI, respectively. The LCI assay was performed using an established procedure (Chen et al, 2008;Huang et al, 2023). To quantify the signal intensity of luciferase activity, a Pro35S::RLUC was co-expressed in each combination as an internal control and the luciferase activity was analyzed by using a Firefly and Renilla Luciferase Assay Kit (Promega, Beijing, China) on a microplate reader.…”
Section: Analysis Of Protein-protein Interactionsmentioning
confidence: 99%
“…It is divided into four classes (KCS1-like, FAE-like, FDH-like, CER6) or eight subclasses (α, β, γ, δ, ε, ζ, η, and θ) according to their phylogeny and duplication history ( Costaglioli et al., 2005 ; Joubès et al., 2008 ). Previous studies have demonstrated that they catalyze the formation of diverse VLCFAs and play important roles in Arabidopsis developmental and metabolic processes, such as cuticular wax production ( AtKCS s 1 , 2 , 3 , 4 , 5 , 6 , 9 , 16 and 20 ) ( Todd et al., 1999 ; Fiebig et al., 2000 ; Kim et al., 2013 ; Hegebarth et al., 2017 ; Kim et al., 2021 ; Huang et al., 2022 ; Huang et al., 2023 ), suberin metabolism in roots ( AtKCS s 2 , 9 and 20 ) ( Franke et al., 2009 ; Lee et al., 2009 ; Kim et al., 2013 ), oil biosynthesis in seeds ( AtKCS18 ) ( James et al., 1995 ), and development of epidermis ( AtKCS10 and AtKCS13 ) ( Gray et al., 2000 ; Pruitt et al., 2000 ). Moreover, several AtKCS genes have been confirmed to play crucial roles in abiotic stress responses and tolerance.…”
Section: Introductionmentioning
confidence: 99%